1994
DOI: 10.1103/physrevb.50.7567
|View full text |Cite
|
Sign up to set email alerts
|

Surface phase transition and interface interaction in the α-Sn/InSb{111} system

Abstract: Thin films of a-Sn were epitaxially grown on InSb(111)A and InSb(111)Bsubstrates at room temperature. %'e studied growth modes and phase transitions of the films by using refiection high-energy electron diffraction and Auger electron spectroscopy. The films on InSb(111)A grew in biatomic layer-bylayer modes. Characteristic growth features for Sn/InSb(111)B were due to the segregation of Sb to the a-Sn film surface. Thus, we used the Sn/InSb(111) A system to examine the stability of the films as a function of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
60
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 12 publications
3
60
0
Order By: Relevance
“…1(f)) along the red dashed arrow shown in Fig. 1(c) indicates a similar lattice constant (0.430.01 nm) with substrate which is slightly smaller than either Sn(111) surface [24] or freestanding stanene (0.468 nm) [14]. The smaller lattice constant suggest the existence of compressive strain in stanene on Sb(111), which may cause a slight fluctuation in the buckling degree of Sn atoms, and it explains the inhomogeneity in the image contrast in Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1(f)) along the red dashed arrow shown in Fig. 1(c) indicates a similar lattice constant (0.430.01 nm) with substrate which is slightly smaller than either Sn(111) surface [24] or freestanding stanene (0.468 nm) [14]. The smaller lattice constant suggest the existence of compressive strain in stanene on Sb(111), which may cause a slight fluctuation in the buckling degree of Sn atoms, and it explains the inhomogeneity in the image contrast in Fig.…”
mentioning
confidence: 96%
“…1(g). Further deposition of Sn atoms on Sb(111) with coverage exceeding one monolayer will form 22 reconstruction on the top of Sn layer, which is similar to the -Sn(111) grown on InSb(111) substrate [24,25]. Therefore, the growth of tin on Sb(111) should be layer-by-layer mode.…”
mentioning
confidence: 99%
“…1(c)) demonstrates a good film quality. The pattern also reveals a 3×3 reconstruction, which is known to exist on the -Sn(111) face [30]. Fig.…”
mentioning
confidence: 99%
“…Prior studies have shown that stanene films can be prepared by depositing Sn on selected substrates including Bi2Te3, Sb(111), and Bi(111) [20][21][22] [25,26]. Here, using reflection high-energy electron diffraction (HREED) and angle-resolved photoemission spectroscopy (ARPES), we show that a high-quality single Sn layer can be grown on the (111)B-face of InSb (the B face is Sb-terminated, while the A face is In-terminated).…”
mentioning
confidence: 99%